Relations between Israel and USSR in 1956—1957: according to Documents of State Archives of Israel - Yu. I. Kostenko; V. M. Morozov (Научный диалог, 2021)
Authors of the article analyze the relations between Israel and the USSR in 1956-1957. Particular attention is paid to Israel’s efforts to ensure national security, the consequences of the Sinai campaign and the “problem of the Jews of the USSR”. The relevance of the study is due to the importance of these issues for bilateral relations. The opinion that the USSR has passed to unconditional sup-port of the Arabs and that this policy will not change is commented on the opinion that has taken root in Israel. It is noted that Israel’s victory in the 1956 Sinai campaign dealt a blow to the positions of the USSR in the Arab world, but the Israeli leadership realized that the USSR would not agree with the loss of these positions. It is shown that Israel strove to maintain an “atmosphere of dialogue”, to develop trade relations, cultural and scientific ties with the USSR, fearing that the position of the USSR on the Middle East would affect the position of Soviet Jews. The novelty of the research lies in the fact that the authors used un-published and previously untranslated archival materials, which made it possible to look at the events through the eyes of Israeli diplomacy, to understand the reasoning for decision-making. The authors conclude that the events of 1956 influenced the way the country’s leadership perceived Israel’s place in international relations. It is emphasized that at this time Israel finally established itself in a pro-Western foreign policy orientation.